The spider genus Cnodalia (Araneae: Araneidae) in China - Mi, Xiao-Qi; Peng, Xian-Jin; Yin, Chang-Min (Zootaxa, 2010)
Two new species, both from China, of the previously monotypic araneid genus Cnodalia Thorell, 1890 are described and illustrated: Cnodalia quadrituberculata n. sp. and Cnodalia flavescens n. sp.